2014
DOI: 10.1111/cen.12540
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional associations of acylation stimulating protein (ASP) and adipose tissue gene expression with estradiol and progesterone in pre‐ and postmenopausal women

Abstract: Our results are consistent with the concept that sex hormones differentially influence circulating ASP and adipose tissue gene expression of its related proteins in a depot-specific manner. ASP may play a role in the regulation of regional fat metabolism through interactions with sex hormones in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Elevated ASP and decrease Orexin-A level lead to an increase triglyceride storage in adipose tissue are responsible for diabetes and cardiovascular disease that are associated with obesity and metabolic disorder. 16, 26-28 Likewise, In the current study, obese women with metabolic syndrome have higher triglyceride was reported that high ASP level and low Orexin-A level are consequence of abnormal lipid metabolism. Since all of the subject in the current study were highly probable that these changes occur earlier in obesity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Elevated ASP and decrease Orexin-A level lead to an increase triglyceride storage in adipose tissue are responsible for diabetes and cardiovascular disease that are associated with obesity and metabolic disorder. 16, 26-28 Likewise, In the current study, obese women with metabolic syndrome have higher triglyceride was reported that high ASP level and low Orexin-A level are consequence of abnormal lipid metabolism. Since all of the subject in the current study were highly probable that these changes occur earlier in obesity.…”
Section: Discussionsupporting
confidence: 54%
“…Indian women have excess body and abdominal fat these are ethnic factors affect the interaction between abdominal adiposity and metabolic risk marker. 14,15 Studies have shown reported that ASP and Orexin-A are more susceptible to metabolic disturbance and the ratio of both might be responsible for the severity of the obesity 16,17 and regulation of energy homeostasis by fat storage in adipose tissue 17,18 ASP is increased and Orexin-A is decreased in obesity. Hence, imbalance in energy expenditure and energy intake, are important pathophysiological factors for the obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ASP knockout mice demonstrated delayed TG clearance, which was more pronounced in males, suggesting gender differences in ASP mediated postprandial TG clearance [ 2 ]. Evidence that links sex hormones to ASP variations is limited and mainly consists of results that show significant associations between plasma ASP and circulating female hormone levels in humans [ 13 , 15 , 30 ]. Direct effects of female hormones on ASP production and function were shown in vitro [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that ASP levels followed the same pattern of increasing progesterone levels from the follicular towards the luteal phase where ASP levels became significantly elevated [ 13 ]. Furthermore, a recent study showed that circulating progesterone levels correlated positively with complement C3 (ASP precursor) gene expression in adipose tissue [ 30 ]. Another human study showed that hormone replacement treatment in postmenopausal women increased circulating C3 levels; however, differential effects of female hormones were not determined [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cylation-stimulating protein (ASP) is an adipokine synthesized within adipocytes environment due to adipocyte differentiation; it acts as autocrine molecules on adipocytes to increase glucose transport, fatty acid esterification, and then triglyceride (TG) synthesis. [1] The effects of ASP are mediated by a G-protein coupled receptor called C5 L2 receptor leading to inhibition of hormone sensitive lipase and augmentation of insulin action on adipocyte. [2] Generation of ASP occurs through activation of alternative pathways to complement system, when complement C3 interacts with adipsin during tissue injury C3a will be produced which is quickly cleaved by plasma carboxypeptidase to generate C3adesArg which called ASP due to its noticeable action on TG synthesis in adipocytes.…”
Section: Introductionmentioning
confidence: 99%